A case study of acute toxicity after consumption of kokkumarundhu (carbamate compounds) - Vishal K.; R. Ganesh; S. Abirami; R. J. Charu Latha (International Journal Of Community Medicine And Public Health, 2026)
Acute poisoning due to ingestion of toxic compounds remains an important medical emergency associated with significant morbidity and mortality. Traditional herbal preparations and locally used substances are increasingly being implicated in poisoning casesbecause of their easy accessibility and lack of awareness regarding their toxic effects. Kokkumarundhuis a traditional paste preparation containing rice and other grains mixed with carbamate compounds and may produce toxic manifestations after ingestion.The presence of associated substance abuse and alcohol consumption may further complicate the clinical presentation and management of such cases. We report the case of a 20-year-old male with a history of chronic smoking, alcohol dependence, and suspectedmulti-substance abuse who presented to the emergency department with complaints of sudden onset abdominal pain and dizziness following three days of binge alcohol intake. The patient denied nausea, vomiting, chest pain, and dyspnea but complained of chills. Further history from family members revealed ingestion of kokkumarundhuapproximately four hours prior to presentation. On examination, the patient was conscious, alert, oriented, and afebrile with mild hypertension (BP: 170/60 mmHg). Investigations including serum electrolytes, cardiac biomarkers, and echocardiography were within normal limits, indicating stable cardiovascular status. The acute clinical manifestations were likely due to the combined effects of kokkumarundhuingestion, alcohol consumption, and chronic substance use. Early supportive treatment with intravenous fluids, thiamine, atropine, and close monitoring was initiated to prevent deterioration. This case highlights the importance of prompt recognition and early management ofacute toxicity, particularly in patients with associated substance abuse, to prevent complications and ensure favorable outcomes